Masificación del fútbol con fundamental ténicos-metodológicos en los estudiantes del 8vo, 9no y 10mo año de educación básica, en el Colegio Técnico Nacional Carmen Mora de Encalada del cantón Pasaje, en el periodo lectivo 2012-2013. - Espinoza Sarmiento, Jonathan Hernán (2013)
The investigation pursuant to its nature and characteristics is eminently descriptive literature and assumes characteristic to the extent that assumes descriptive and bibliographic characteristics of youth football, the specific objectives to meet research allowed.